Inheritance and innovation: the cross-cultural application of Chinese traditional auspicious patterns in sustainable tourist souvenirs - Yao, Hong; Alli, Hassan; Shaari, Nazlina (Global Academic Excellence (M) Sdn Bhd, 2024)
This paper discusses the cross-cultural application of Chinese traditional auspicious patterns in sustainable tourist souvenirs. It aims to explore how to combine traditional cultural elements with the concept of sustainable development to promote the sustainable development of tourism. First introduces the history and cultural connotation of Chinese traditional auspicious pattern, through the auspicious pattern cultural significance, historical background and modern application, this paper puts forward the importance of traditional auspicious pattern in sustainable tourism souvenir design, and then analyses the environmental problems of the current tourist souvenir market, then puts forward the traditional auspicious pattern applied to tourism souvenirs innovative ideas and methods, and combined with the perspective of cross-cultural communication, discusses the traditional cultural symbol in the inheritance and innovation of contemporary tourism industry, promote the sustainable development of tourism. This paper adopts the research method of qualitative analysis, through case analysis and empirical research, summarizes the application strategy of Chinese traditional auspicious patterns in sustainable tourism souvenirs, and puts forward relevant development suggestions and prospects to promote the sustainable development of tourism.